Regional decomposition of CO2 emissions in the world: a cluster analysis - Alcántara, Vicent; Duarte, Rosa; Obis, Teresa (Sociedad y Economía, 2005)
The purpose of this paper is to study the possible differences among countries as CO2 emitters and to examine the underlying causes of these differences. The starting point of the analysis is the Kaya identity, which allows us to break down per cápita emissions in four components: an Índex of carbón intensity, transformation efficiency, energy intensity and social wealth. Through a cluster analysis we have identifica five groups of countries with different behavior according to these four factors. One significant finding is that these groups are stable for the period analyzed. This suggests that a study based on these components can characterize quite accurately the polluting behavior of individual countries, that is to say, the classification found in the analysis could be used in other studies which look to study the behavior of countries in terms of CO2 emissions in homogeneous groups. In this sense, it supposes an advance over the traditional regional or rich-poor countries classifications.